Headache: A potential sequela of posterior reversible encephalopathy syndrome - M. Rodrigo-Gisbert; E. Caronna; A. Alpuente; M. Torres-Ferrús; P. Pozo-Rosich (Neurología, 2025)
Introduction: Posterior reversible encephalopathy syndrome (PRES) is a neurological disorder consisting in cerebrovascular dysregulation with acute neurological symptoms, including headache. However, there is a paucity of data that point to headache as a sequela of PRES. We aimed to explore its prevalence, characteristics, and impact. Methods: We retrospectively included all consecutive patients with PRES attended at our institution from April 2018 to January 2022. We collected demographic and clinico-radiological data from the acute phase. During a mean follow-up time of 16 (14) months, we assessed the presence of headache after PRES and evaluated its impact using validated questionnaires. Results: Of the 27 cases detected, after excluding 16 patients (11 deceased and 5 lost to follow-up), we evaluated 11 patients with a mean age of 38 (14) years; 63.6% were female. After PRES resolution, 9/11 (81.8%) patients presented headache, with migraine-like features in 8/9 (88.9%). Seven patients completed validated questionnaires; on the Migraine Disability Assessment scale, 71.4% (5/7) had moderate–severe disability. The Short Form-36 Health Survey dimensions of general health, physical role, and vitality reflected a deterioration in the quality of life. Conclusions: Our data suggest that headache is a potential sequela of PRES that could imply subsequent disability. Migraine-like features point to the existence of shared pathophysiological mechanisms with migraine, which may mainly involve vascular and endothelial functions; however, more studies are needed. Resumen: Introducción: El síndrome de encefalopatía posterior reversible (PRES) se caracteriza por una desregulación cerebrovascular reversible, en el que la cefalea es un síntoma cardinal. Dado que la cefalea como secuela del PRES no ha sido sistemáticamente estudiada, nuestro objetivo fue explorar su prevalencia, características e impacto. Métodos: Retrospectivamente se registraron 27 pacientes con diagnóstico de PRES entre abril-2018 y enero-2022. Se describieron las características demográficas y clínicorradiológicas de la hospitalización. Se evaluó la presencia de cefalea e impacto mediante la escala Migraine Dissability Assessment Scale (MIDAS), Headache Impact Test (HIT-6), SF36_v2, Hospital Anxiety and Depression Scale (HADS) y Pittsburgh Sleep Quality Index (PSQI). Resultados: Se incluyeron 27 pacientes con diagnóstico de PRES, tras excluir la mortalidad intrahospitalaria y las pérdidas de seguimiento, se evaluaron 11 pacientes con una edad media de 38 ± 14 años, el 63,6% eran mujeres. De ellos, 3/11 (27,3%) tenían antecedentes de migraña episódica de baja frecuencia. Tras la resolución del PRES, 9/11 pacientes (81,8%) tenían cefalea, siendo episódica (8/9, 88,9%) y de características migrañosas (8/9, 88,9%). Siete pacientes completaron la totalidad de las escalas. El 71,4% (5/7) presentaba una discapacidad moderada/grave en la escala MIDAS. En la SF36_v2, las dimensiones de salud general, rol físico y vitalidad reflejaban un deterioro en la calidad de vida. A parte de la cefalea, no se reportaron otras secuelas relevantes salvo epilepsia estructural en 2 pacientes. Ningún paciente recibió tratamiento específico para la cefalea. Conclusión: Nuestros datos sugieren una elevada prevalencia de cefalea como potencial secuela del PRES. Las características migrañosas podrían sugerir un mecanismo fisiopatológico común con la migraña que involucre disfunción vasculo-endotelial.